STRATEGI COPING TERHADAP STRES KERJA DI LINGKUNGAN KARYAWAN STAIN MALANG - Ardani, Tristiadi Ardi (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2004)
Background: Stres effect of work represent an problems which later will become big problems in the field of safety and health of work Because stres have undesirable impact like for example accident of work, disease related to work and also health of management and mental. Preventive of stres require to be conducted comprehensively good at organizational storey; level and also at individual storey; level and also entangle role various sector and also various professional circlewhich is discipline multi. Method: Analysis Data of kuantitif in this research of method used analyse dwivariat test student t between program group of SPS 2000 from Sutrisno Hadi and of Yuni Pamardiningsih UGM Version of IBM / in, Copyrights (c) 2002. While with data collecting method qualitative by interview at employees of STAIN Malang. Result: From result of koputasi obtained by result of higher woman group average of men average with woman group average number equal to 116.000 while its men group [of] him equal to 113.778. From result of test of t which is to be obtained by value of p equal to 0.504. There by can be said that by there no different among woman and men in strategy of coping in face of work stres. In this research to know technique reliabilitas taken is analysis of varians of Hoyt. Of computing test by using program of SPS of Sutrsino Hadi and of Yuni Pamardiningsih UGM Version of IBM / in, Copyrights (c) 2002 obtained result of tt r equal to 0.832, p equal to 0.000 meaning the appliance reliabilitas can be pledged. While with data collecting method qualitative by interview at employees obtained by result of that there is indication of is existence of stres work at employees. Conclusion: that no different between woman and men in strategy of coping in face of work stres. Method data collecting quantitatively with enquette at employees obtained by result of that there is indication of is existence of stres work at employees. As for strategy of coping in face of stres to men employees most chosening to smoke, but there is also employees chosening to walk along to watch television and others when is face work. While at woman employees some people chosen to discuss with friend one friend or office of other office and some of again chosen to walk along when stres face work. Keyword: strategy of coping, stres work.